2016
DOI: 10.3389/fpubh.2016.00019
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Occupational Exposure to Lead and Hearing Loss in a Cross-Sectional Survey of Iranian Workers

Abstract: ObjectivesOtotoxic effect of exposure to lead has been reported by many researchers. This study was undertaken with a view to investigate the relationship between blood lead level (BLL) and hearing loss in workers in a lead-acid battery manufacturing plant in Tehran, Iran.MethodsIn a cross-sectional study, 609 male workers were recruited from different locations in the factory. Association between BLL and hearing loss in different frequencies were measured. Relationships were analyzed by logistic regressions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The link between environmental or occupational exposure to lead and hearing impairment has been well documented (Choi et al, 2012; Forst et al, 1997; Ghiasvand et al, 2016; Pawlas et al, 2015). Though lead induces oxidative damage to mediate its adverse health effects (Bhatti et al, 2009; Dobrakowski et al, 2017) and the inner ear is highly susceptible to oxidative damage (Henderson et al, 2006; Poirrier et al, 2010) the potential role of cochlear oxidative stress in lead-induced auditory dysfunction is yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The link between environmental or occupational exposure to lead and hearing impairment has been well documented (Choi et al, 2012; Forst et al, 1997; Ghiasvand et al, 2016; Pawlas et al, 2015). Though lead induces oxidative damage to mediate its adverse health effects (Bhatti et al, 2009; Dobrakowski et al, 2017) and the inner ear is highly susceptible to oxidative damage (Henderson et al, 2006; Poirrier et al, 2010) the potential role of cochlear oxidative stress in lead-induced auditory dysfunction is yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Upon absorption they accumulate in soft tissues and bones and alter cellular homeostasis [8,9]. Long term exposure to heavy metals, such as lead, cadmium, cobalt, arsenic, and mercury, can cause auditory dysfunction [10][11][12][13][14]. Particularly, exposure to cadmium and lead damages the sensory receptor cells in the cochlea [15,16] and induces oxidative stress in several other organs [17][18][19].…”
Section: Heavy Metalsmentioning
confidence: 99%
“…These findings are in agreement with the observations of Ghiasvand et al who in a population of occupational lead exposure found a significant association between level of lead exposure and pure tone audiometry results. 32 Kang et al in a recent study based on Korean National Health and Nutritional Examination Survey results also found that even exposure to low-level lead is a risk factor for highfrequency hearing loss. 33 The findings of present study thus show that lead exposure could be a possible reason for hearing loss in young patients having no other plausible cause.…”
Section: Discussionmentioning
confidence: 94%